The Role of Women in Luke's Gospel: An Intersectional Analysis of Gender and Power Dynamics - Gunasekera, Suranga I. A. (Faculty of Humanities, University of Kelaniya, 2023)
Feminist scholarship on Luke's Gospel has revealed that its portrayal of women is far from liberating, contrary to popular belief. On the other hand, masculinity studies suggest that Luke's depiction of Jesus conforms to gender roles in the Roman Empire. This paper explores these two insights and argues that Luke's portrayal of men depends on women's erasure. By examining the characterization of women at the tomb and the relationship between Jesus and the apostles in Luke 23:26-24:53, it is argued that the role of women in the events of crucifixion, burial, and resurrection is primarily to support the power claims of the male apostles and legitimize their mission. The paper highlights that the absence of women in the final appearances of Jesus foregrounds a homosocial relationship among the male apostles, where their male bonding and solidarity take precedence over the representation of women. The paper connects the gender and power dynamics in Luke's Gospel with the concept of homosociality to argue that the text prioritizes male relationships over female representation. Thus, this paper offers an intersectional analysis of gender and power dynamics in Luke's Gospel, highlighting how the portrayal of women bolsters the power claims of male apostles. The study reveals that the absence of women in the final appearances of Jesus is not incidental but rather a deliberate attempt to prioritize male relationships over female representation. This paper adds to the growing body of literature that challenges the assumption that Luke's Gospel is a liberating text for women, underscoring the importance of intersectional analysis in biblical scholarship.
Keywords: Feminist, Gender, Homosociality, Luke's Gospel, Women